2016
DOI: 10.1021/jacs.5b11713
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bifunctional Oxygen Catalysis in Strained LaNiO3 Perovskites

Abstract: ABSTRACT:Strain is known to greatly influence low temperature oxygen electrocatalysis on noble metal films, leading to significant enhancements in bifunctional activity essential for fuel cells and metal-air batteries. However, its catalytic impact on transition metal oxide (TMO) thin films, such as perovskites, is not widely understood. Here, we epitaxially strain the conducting perovskite LaNiO 3 to systematically determine its influence on both the oxygen reduction (ORR) and oxygen evolution reaction (OER).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
346
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(364 citation statements)
references
References 42 publications
17
346
1
Order By: Relevance
“…Therefore, the design of perovskite catalysts with surface active oxygen, calls for the development of dedicated computational tools in order to better understand these complex mechanisms. Moreover, LaNiO 3 perovskite, previously discussed as a potential charge transfer material (Figure 5d), was also proposed by computation to involve surface oxygen as the active site [7]; even though this compound was previously studied for its propensity for diffusion of oxygen vacancies [80], this assertion remains to be experimentally demonstrated.…”
Section: Low Temperature Oxygen Evolution Reactionmentioning
confidence: 99%
“…Therefore, the design of perovskite catalysts with surface active oxygen, calls for the development of dedicated computational tools in order to better understand these complex mechanisms. Moreover, LaNiO 3 perovskite, previously discussed as a potential charge transfer material (Figure 5d), was also proposed by computation to involve surface oxygen as the active site [7]; even though this compound was previously studied for its propensity for diffusion of oxygen vacancies [80], this assertion remains to be experimentally demonstrated.…”
Section: Low Temperature Oxygen Evolution Reactionmentioning
confidence: 99%
“…Recently, Lee et al reported the strained LaNiO 3 for the enhanced bifunctional ORR/OER catalysis using different lattice-mismatched substrates to control strain degree from −2.2% to 2.7% (Figure 7a). [59] They found that when LaAlO 3 (LAO) is used as substrate, the produced small strain of −1.2% in LaNiO 3 can lead to the enhanced bifunctional ORR/OER compared to other strained samples and pristine LaNiO 3 (Figure 7b,c). When ORR and OER activities under the overpotentials of 0.4 V are compared (Figure 7d), the bifunctional activity drastically increases with compressive strain.…”
Section: Strain Engineeringmentioning
confidence: 99%
“…Due to the similarity in the chemistry of the Co-based perovskites, the discrepancy is unlikely to be caused by doping of divalent cations and requires further studies. Lastly, LaNiO 3 on various substrates was found active for oxygen reduction [60,132]. In future work, it would be highly desirable to quantify the product yield of these surfaces in the absence of potential co-catalysts such as carbon.…”
Section: Activity Metricsmentioning
confidence: 99%